Understanding resale prices of private properties in Singapore : a hedonic model approach - Phang, Merrick Jun Yi (Nanyang Technological University, 2021)
The aim of this paper is to investigate the effect that different housing variables have on the various resale housing lease types in Singapore’s housing market. This paper focuses on the private housing market where there appears to be research gaps and explores factors, which could potentially influence resale prices. More pertinently, the paper looks at how each variable can influence and impact the prices of 99-year lease and freehold lease resale properties differently. Our model adopts the hedonic pricing model, while taking into consideration other lease variables such as housing area. From the data extracted, results have shown that the various amenities have varying impact on resale property prices, depending on their lease types. MRTs and bus stops have a positive correlation while shopping malls have a negative correlation for both the freehold and 99-year leasehold market. An increase in distance from the Central Business District (CBD) and a greater number of years since completion of the property have a negative relationship with housing prices.